Pendekatan Customer Relationship Management Untuk Fungsi Strategi Pemasaran dan Peningkatan Brand Kopi Go Karawang - Yusuf Bahtiar; Wahyudin Wahyudin (Peneliti.net, 2022)
Marketing is one of the important things in the sales system, good marketing will bring big profits for the company. Companies are competing in preparing marketing programs that will be carried out in order to maintain the existence of their company. In addition to a good marketing program, the company must also be supported by the management of a balanced product line and brand, such as the Go Karawang Coffee shop which provides important points in its marketing program so that its products can compete and survive with its competitors. The selection of a brand or brand that is easy to remember by the public provides a plus point for the company. In addition, it is implemented with a system to increase the brand through internet media by collaborating on food/beverage delivery services. From the results of the interview, it was found that the relationship between marketing product design and product line and brand management gave good results for the sales of Kopi Go Karawang products